The Physiological Mechanism of Arbuscular Mycorrhizal in Regulating the Growth of Trifoliate Orange (Poncirus trifoliata L. Raf.) Under Low-Temperature Stress - Changlin Li; Xian Pei; Qiaofeng Yang; Fuyuan Su; Chuanwu Yao; Hua Zhang; Zaihu Pang; Zhonghua Yao; Dejian Zhang; Yan Wang (Horticulturae)
In recent years, low temperature has seriously threatened the citrus industry. Arbuscular mycorrhizal fungi (AMF) can enhance the absorption of nutrients and water and tolerance to abiotic stresses. In this study, pot experiments were conducted to study the effects of low-temperature stress on citrus (trifoliate orange, Poncirus trifoliata L. Raf.) with AMF (Diversispora epigaea D.e). The results showed that AMF inoculation significantly increased plant growth, chlorophyll fluorescence, and photosynthetic parameters. Compared with 25 °C, −5 °C significantly increased the relative conductance rate and the contents of malondialdehyde, hydrogen peroxide, soluble sugar soluble protein, and proline, and also enhanced the activities of catalase and superoxide dismutase, but dramatically reduced photosynthetic parameters. Compared with the non-AMF group, AMF significantly increased the maximum light quantum efficiency and steady-state light quantum efficiency at 25 °C (by 16.67% and 61.54%), and increased the same parameters by 71.43% and 140% at −5 °C. AMF also significantly increased the leaf net photosynthetic rate and transpiration rate at 25 °C (by 54.76% and 29.23%), and increased the same parameters by 72.97% and 26.67% at −5 °C. Compared with the non-AMF treatment, the AMF treatment significantly reduced malondialdehyde and hydrogen peroxide content at 25 °C (by 46.55% and 41.29%), and reduced them by 28.21% and 29.29% at −5 °C. In addition, AMF significantly increased the contents of soluble sugar, soluble protein, and proline at 25 °C (by 15.22%, 34.38%, and 11.38%), but these increased by only 9.64%, 0.47%, and 6.09% at −5 °C. Furthermore, AMF increased the activities of superoxide dismutase and catalase at 25 °C (by 13.33% and 13.72%), but these increased by only 5.51% and 13.46% at −5 °C. In conclusion, AMF can promote the growth of the aboveground and underground parts of trifoliate orange seedlings and enhance their resistance to low temperature via photosynthesis, osmoregulatory substances, and their antioxidant system.